Encyclopedia of Environmental Microbiology 2003
DOI: 10.1002/0471263397.env208
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizae: Ectomycorrhizal Fungi

Abstract: Host–Fungus Associations Structure and Function Ecology of Ectomycorrhizae Ecosystem Functions Physiology Practical Applications in Forestry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Vogt et al (1983) reported that 88% of Douglas-fir root tips were infected with mycorrhizal fungi in low fertility sites of western Washington, USA. The low nutrient status of these soils is likely a driver of the highly mycorrhizal nature of these systems, as mycorrhize greatly enhance the ability of infected hosts to access nutrients, and aid in decomposition of recalcitrant substances (Cairney and Chambers 1999; Molina et al 2002;Read and PerezMoreno 2003). It is very possible that at our site much of the belowground litter input comes not from roots directly, but from mycorrhizae associated with roots.…”
Section: Belowground Litter Contributionmentioning
confidence: 99%
“…Vogt et al (1983) reported that 88% of Douglas-fir root tips were infected with mycorrhizal fungi in low fertility sites of western Washington, USA. The low nutrient status of these soils is likely a driver of the highly mycorrhizal nature of these systems, as mycorrhize greatly enhance the ability of infected hosts to access nutrients, and aid in decomposition of recalcitrant substances (Cairney and Chambers 1999; Molina et al 2002;Read and PerezMoreno 2003). It is very possible that at our site much of the belowground litter input comes not from roots directly, but from mycorrhizae associated with roots.…”
Section: Belowground Litter Contributionmentioning
confidence: 99%
“…For instance, the fungi forming ectomycorrhizal symbioses number over 5000 species [1]. Analysis of natural ectomycorrhizal fungal communities traditionally has been a laborious, highly-skilled process with heavy reliance on gross morphological characterization of the ectomycorrhizal root-tips.…”
Section: Introductionmentioning
confidence: 99%
“…Primers allowing simultaneous analysis of all the fungal phyla which are involved in ectomycorrhizal symbioses would be a useful tool in studying the ecology of these fungi. Of particular interest for such work is the division Dikaryomycota, which includes the subdivisions Basidiomycotina and Ascomycotina, and encompasses all ectomycorrhizal fungi [1]. …”
Section: Introductionmentioning
confidence: 99%